"Ora tutto è finito!" female development in the novels of Giovanni Verga - Amatangelo, Susan (Spunti e Ricerche, 2016)
In three novels that span his career, I Carbonari della montagna, Storia di una capinera, and Mastrodon Gesualdo, Verga portrays three young women of different characters and conditions who find themselves on the threshold of the adult world. However distinctive their stories, their lives are linked by a pattern: all three enjoy a period of freedom that they are forced to leave behind as they take their place in society, through marriage or the taking of religious vows; from this point forward, their lives, and stories, begin to unravel, eventually ending in tragedy.